The dynamic landscape of BRCA1 reversion mutations from indel to SNV in a patient with ovarian cancer treated with PARP-inhibitors and immunotherapy - Jacob, Saya L. (Heliyon, 2020)
BACKGROUND: Reversion mutations of somatic BRCA mutations are an important source of resistance within ovarian cancer. Furthermore, these reversion mutations are known to change over the course of treatment. Better understanding of the mechanisms leading to reversion mutations and the role of serial ctDNA collection in detecting changes to overall landscape of resistance mutations over time is needed to guide treatment in the metastatic setting. METHODS: Here we study a case of metastatic ovarian cancer undergoing multiple lines of treatment with collection of three serial ctDNA samples. These samples were analyzed by Guardant Health next generation sequencing to detect somatic alterations and their associated mutant allele frequency (MAF) as % cfDNA. RESULTS: Analysis of our initial ctDNA collection, taken during PARP-inhibitor therapy, revealed a nonsense BRCA-1 mutation (c. 2563C > T p. Q855∗), consistent with the BRCA 1 somatic mutation detected on tumor tissue analysis. Initial analysis also revealed a reversion mutation (c.2535_2576del) resulting in an in-frame deletion of the somatic BRCA-1 alteration. The second collection, taken while still on PARP-inhibitor therapy, re-demonstrated this indel reversion mutation along with a second indel reversion mutation (c.2546_2587del), again resulting in an in-frame deletion of the somatic BRCA-1 mutation. The final ctDNA, collected upon initiation of immunotherapy, revealed 4 novel SNV reversion mutations (c.2564A > C, c.2564A > T, c.2565G > T, and c.2565G > C). These SNV reversion mutations result in missense amino acid changes rather than insertions or deletions within the BRCA-1 somatic mutation. The previous indel reversion mutations were no longer detected. CONCLUSIONS: This study illustrates the role of serial ctDNA analyses in the detection of resistance mutations and the dynamic nature of reversion mutations with multiple lines of treatment. While other studies have described both indels and SNVs that occur in tandem, a change in the types of reversion mutations detected across changing therapies has never before been described. Further studies regarding the unique selective pressures arising from use of multiple types of therapy is needed to fully explain this phenomenon.